2008
DOI: 10.1111/j.1365-2982.2008.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

A mixture of Escherichia coli (DSM 17252) and Enterococcus faecalis (DSM 16440) for treatment of the irritable bowel syndrome – A randomized controlled trial with primary care physicians

Abstract: Therapy trials with bacterial compounds in irritable bowel syndrome (IBS) have produced conflicting results. This study was performed in 1988 and 1989, and was re-analysed according to current IBS standards. Two hundred ninety-seven patients with lower abdominal symptoms diagnosed as IBS were treated for 8 weeks by the compound ProSymbioflor((R)) (Symbiopharm GmbH, Herborn, Germany), an autolysate of cells and cell fragments of Enterococcus faecalis and Escherichia coli, or placebo in a double-blinded, randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 28 publications
1
103
1
2
Order By: Relevance
“…Following a full-paper review, we excluded 8 further studies due to various reasons: only 1 study reported data from prebiotic treatment, 29 1 study did not use a probiotic in a strict sense (no living bacteria), 30 2 were microbial investigations of earlier studies, 31,32 2 were single-blinded, 33,34 and 2 were uncontrolled interventions. 35,36 Based on hand-searches of the published meta-analyses, we added 3 more studies, [37][38][39] resulting in a total of 55 articles.…”
Section: Resultsmentioning
confidence: 99%
“…Following a full-paper review, we excluded 8 further studies due to various reasons: only 1 study reported data from prebiotic treatment, 29 1 study did not use a probiotic in a strict sense (no living bacteria), 30 2 were microbial investigations of earlier studies, 31,32 2 were single-blinded, 33,34 and 2 were uncontrolled interventions. 35,36 Based on hand-searches of the published meta-analyses, we added 3 more studies, [37][38][39] resulting in a total of 55 articles.…”
Section: Resultsmentioning
confidence: 99%
“…If the probiotics are shown to be effective as they have been in initial studies [21], they should be used in place of the current medications when possible. Probiotics are healthy bacteria that are a part of the human digestive tract; using them to treat gastrointestinal disorders and help return the gut to a state of homeostasis is preferable to introducing medications that will further eradicate the healthy gut bacteria and increase the risk of more serious gastrointestinal distress [30][31][32]. As Horveth discusses, individual strains need to be tested first and then probiotic combination therapies to develop effective probiotics to treat gastrointestinal disorders [21].…”
Section: Discussionmentioning
confidence: 99%
“…Only three published trials assessed ADEs related to probiotics in IBS in any systematic or standardized way. (27,29,34) A recent metaanalysis(39) showed a pooled relative risk (RR) for an adverse event of any type across all published trials of 1.21 (95% CI 1.02-1.44) and number needed to harm was 35. 16.5% of patients in all trials had an ADE on probiotics, compared with 13.8% of controls.…”
Section: Ibsmentioning
confidence: 99%
“…First, we constructed a dataset using all existing clinical trials that reported both efficacy and adverse drug events for both IBS (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) or IBD(40-49), as described in Figure 1 and Table 1. We sampled across the 95% confidence intervals for each trial weighted by the size of the trial (larger trials had a larger share of sampling).…”
mentioning
confidence: 99%